(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article is devoted to the analysis of the functioning of ideological codes in the content of Ukrainian commercial TV advertising, their correlation with slogans and the determination of dominant impact indicators. The author determined that the concepts of «ideological code» and «slogan» are in the same definitive field, but they represent the whole-part ratio, because the slogan is the ideologue of the advertising message and the ideologue is part of the this code. It is established that the markers of ideological codes in slogans are lexemes, which in most cases have the status of key words. Taxonomy of the fixed units was carried out in accordance with the classification of the semiotic signs by Ch. Pierce. They are divided into three groups. The first group contains the slogans, in which the signs-copies are the indicators of ideological codes. The fundamental sign of this group is the lexeme “BEAUTY” and its derivative adjectives. The second group contains the slogans with markers of index status. In this group the indices were such lexemes as “USEFUL”, “SIMPLICITY”, “QUALITY”, “CONVENIENCE”, “COMFORT”, “NOVELTY” and “CLEANLINESS”. Within this group, the author has proved the synonymity of the lexical units “CONVENIENCE”and “COMFORT”. The third group represents the slogans with markers of symbolic status. The author defines that the most active symbols are lexemes “LIFE”, “COUNTRY” (with meaning “MOTHERLAND”) and “FREEDOM”. Within each of the formed groups the specificity of the influence of lexical dominants of ideological codes is shown. It is proved that ideological codes with signs-copies and signs-symbols appeal to the recipient’s emotions, and codes with index signs are directed to the intellectual (rational) sphere of the recipient.